Non-visual colour: A qualitative study of how the totally blind and an achromatope navigate colour in the sighted world - Domicele Jonauskaite; Nina Gierlinger; Klara Geiger; Claudia Busse; Aline Frick; Christine Mohr; Helmut Leder (Acta Psychologica, 2025)
Colour plays an important role in the sighted world, not only by guiding and warning, but also by helping to make decisions, form opinions, and influence emotional landscape. While not everyone has direct access to this information, even people without colour vision (i.e., blind, achromatope) understand the meanings of colour terms and can assign sensory and affective properties to colours. To learn which aspects of colour are transmitted non-visually, and thus, are pertinent to those without colour vision, we conducted qualitative interviews with 11 participants (2 congenitally blind, 2 early blind, 4 late blind, 2 late blind with synaesthesia, and 1 achromatope). Our thematic analysis revealed that all participants had detailed knowledge of colours and displayed opinions and attitudes. Colour was important to them as it allowed to take part in the sighted world, navigate the surroundings, and communicate with the sighted peers. While participants with non-congenital colour vision absence could remember and even visualise colours, colour was more abstract to participants with congenital colour vision absence. This was possibly a reason why colour was not very important to their personal lives. Nonetheless, all our participants associated colours with diverse objects, concepts, and emotions, and also had colour preferences, indicating that semantic (conceptual, symbolic, affective) meanings of colour can be transmitted without direct visual experience. Future quantitative and qualitative studies are needed for a systematic understanding of such connotations in the visually impaired population, and their implications to those who can and cannot see colour.